The Influence of Health Education and Tele-nursing on Folic Acid Adherence in Pregnant Women at Puskesmas Payung Sekaki - Tiara Ananda; Stephanie Dwi Guna; Nopriadi Nopriadi; Febriana Sabrian; Herlina Herlina (CV. Rayyan Dwi Bharata, 2025)
Folic acid is essential for supporting maternal health and fetal development, with a daily requirement of 400 mcg. Folic acid deficiency can cause maternal anemia and fetal growth and development disorders. However, compliance of pregnant women in taking folic acid supplements is still low, due to lack of knowledge and forgetting to take supplements. To improve compliance, health education and telenursing efforts can be applied as an effective solution. This study used a quantitative approach using the one group pretest posttest method. The sample in the study amounted to 34 pregnant women who were taken using non-probability sampling technique with purposive sampling type. The analysis used used the Wilcoxon statistical test. After being given health education and telenursing on the level of compliance of pregnant women drinking folic acid, the results showed an increase in the average compliance between pretest and posttest. The average value before being given health education and telenursing was 2.7353 (SD = 1.24307), after being given health education and telenursing the average increased to 6.7500 (SD = 1.88997). The results of the Wilcoxon test analysis showed that there was an effect of health education and telenursing with the results of p value (0.000) < α (0.005). Providing health education and telenursing has an effect on increasing the compliance of pregnant women in consuming folic acid at Puskesmas Payung Sekaki.